The Optimum Dietary Phenylalanine Requirement of Hybrid Grouper (Epinephelusfuscoguttatus ♀ × Epinepheluslanceolatus ♂) Juveniles: Effects on Growth Performance, Gut Micromorphology, and Antioxidation - Pinxian Yang; Haijiao Wang; Lei Ma; Haoran Yin; Zhanying Zhu; Cong Liu; Wei Huang; Zhiyu Zhou; Xiaoyi Wu; Sehrish Taj (Aquaculture Nutrition)
The optimum phenylalanine (Phe) requirement for hybrid grouper (Epinephelusfuscoguttatus ♀ × Epinepheluslanceolatus ♂) juveniles was determined through an 8-week growth trial. A total of seven isoenergetic (340 kcal per 100 g of dry matter), isonitrogenous, and isolipidic diets were made, containing 8.2 (Phe 8.2), 9.2 (Phe 9.2), 10.1 (Phe 10.1), 11.2 (Phe 11.2), 13.3 (Phe 13.3), 15.2 (Phe 15.2), and 17.3 g/kg (Phe 17.3), respectively. Triplicate tanks of juvenile fish (about 16.7 g/fish) were fed each experimental diet twice daily until apparent satiation. The results indicated that different dietary Phe levels significantly influenced weight gain percentage (WG), feed efficiency (FE), protein efficiency ratio (PER), as well as, productive protein value (PPV). Fish fed Phe 8.2 had the lowest WG or PPV among all experimental treatments. Furthermore, the optimal dietary Phe level increased fold height, width, enterocyte, and microvillus height of fish. The Phe 10.1 group exhibited higher growth hormone (GH) expression in the pituitary compared to other groups. Expression of hepatic insulin-like growth factor-1 (IGF-1) and growth hormone receptor 1 (GHR1) displayed a similar pattern of variation to that of GH. The Phe 13.3 group had lower expression of S6 kinase 1 (S6K1) and target of rapamycin (TOR) than other groups. In addition, fish fed Phe 10.1 had lower levels of nuclear factor erythroid 2 (Nrf2) and heat shock protein 70 (HSP70) in the head kidney, and Cu/Zn-superoxide (Cu/ZnSOD) dismutases in the midgut compared to fish fed other Phe levels. Generally, optimal Phe content in the diet of hybrid grouper was estimated to be 12.7 g/kg of dry matter (27.3 g/kg of dietary protein), and at this level, the feed utilization, gut micromorphology, and immunity of fish were also elevated.